2002
DOI: 10.1590/s0004-282x2002000200005
|View full text |Cite
|
Sign up to set email alerts
|

Fourth ventricle computed tomography indexes: standardisation and characteristics in neurocysticercosis

Abstract: -Objectives: to propose standardisation of fourth ventricle dimensions and to study its characteristics in neurocysticercosis. Method: a control group (CG) constituted by 114 individuals with normal CT, and 80 patients with neurocysticercosis composed the group with neurocysticercosis (GN). Measures of the inner cranial diameter (Cr), fronto-polar distance between both lateral ventricles (FP), antero-posterior (AP) and latero-lateral (LL) fourth ventricle width based the standardisation of six indexes. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…However there mean values showed a significant increase in the last three consecutive age groups (20-> 60) years. These data were consistent with Meese et al (1980), (17) and Agapejev (2002), (10), who found that the fourth ventricle shows a continuous and progressive increase with advancing age. Koller et al (1981), (18), found that the maximal anteroposterior (AP) and laterolateral (LL) width of the fourth ventricle, showed an insignificant increase with advance of age from 20 to 60 years at CT, but they found a significant increase in this parameter thereafter.…”
Section: Linear Measurements Of the Fourth Ventriclesupporting
confidence: 91%
See 4 more Smart Citations
“…However there mean values showed a significant increase in the last three consecutive age groups (20-> 60) years. These data were consistent with Meese et al (1980), (17) and Agapejev (2002), (10), who found that the fourth ventricle shows a continuous and progressive increase with advancing age. Koller et al (1981), (18), found that the maximal anteroposterior (AP) and laterolateral (LL) width of the fourth ventricle, showed an insignificant increase with advance of age from 20 to 60 years at CT, but they found a significant increase in this parameter thereafter.…”
Section: Linear Measurements Of the Fourth Ventriclesupporting
confidence: 91%
“…On the other hand the only index that does not suffer influence of age and sex is the (AP/LL) index. Meese (1980), (17) and Agapejev (2002), (10), confirmed these present data and referred the stability of (AP/LL) index to the volumetric difference in the neuroaxis.…”
Section: Linear Measurements Of the Fourth Ventriclesupporting
confidence: 88%
See 3 more Smart Citations